O olhar para uma população desassistida: determinantes sociais da saúde em Angola - Songa, Marcial António Simão [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Saliba, Tânia Adas [UNESP] (Centro Brasileiro de Estudos de Saúde, 2024)
The objective was to analyze the social determinants of health in Angola. This is a documentary, exploratory and quantitative research, carried out with data from the 2015-2016 Multiple Indicators and Health Survey in Angola. The analyzed variables were: access to drinking water sources; appropriate sanitary facilities; access to electricity; educational level; access to jobs; child mortality rate; prenatal consultations; and vaccination coverage. It was observed that 45.2% of households do not have access to adequate water sources for drinking; 52.9% use inappropriate sanitation facilities, mainly in rural areas; 31% of men aged 15 to 49 were unemployed; 42% of households had access to electricity; 22% of women and 8% of men aged 15 to 49 have never attended school; the estimated infant mortality rate was 44 deaths for every 1000 live births; 44.1% of pregnant women with lower socioeconomic status did not undergo any prenatal consultation; 18.3% of children aged 12 to 23 months and 21% aged 24 to 35 months did not receive any vaccine. It is concluded that there are large gaps in access to social determinants of health, highlighting the need for government efforts in partnership with international organizations to improve the population’s health conditions.

Objetivou-se analisar os fatores determinantes sociais da saúde em Angola. Trata-se de uma pesquisa documental, exploratória e quantitativa, realizada com dados do Inquérito de Indicadores Múltiplos e de Saúde 2015-2016 de Angola. Foram analisadas as variáveis: acesso a fontes de água para beber; instalações sanitárias apropriadas; acesso à eletricidade; nível educacional; acesso a empregos; taxa de mortalidade infantil; consultas pré-natais; e cobertura vacinal. Observou-se que 45,2% dos agregados familiares não têm acesso a fontes de água apropriada para beber; 52,9% utiliza instalações sanitárias não apropriadas, principalmente nas áreas rurais; 31% dos homens de 15 a 49 anos estavam desempregados; 42% dos agregados familiares possuíam acesso à eletricidade; 22% das mulheres e 8% dos homens de 15 a 49 anos nunca frequentaram a escola; a estimativa da taxa de mortalidade infantil foi de 44 mortes para cada 1000 nascidos-vivos; 44,1% das gestantes com menor nível socioeconômico não realizaram nenhuma consulta pré-natal; 18,3% das crianças de 12 a 23 meses e 21% de 24 a 35 meses não receberam nenhuma vacina. Conclui-se que existem grandes lacunas no acesso a determinantes sociais da saúde, evidenciando a necessidade de esforços governamentais em parceria com organismos internacionais para melhorar as condições de saúde da população.
Looking at an underserved population: Social determinants of health in Angola
Keywords: Angola; Health services accessibility; Socioeconomic factors; Public health.; Angola; Acessibilidade aos serviços de saúde; Fatores socioeconômicos; Saúde pública.